New species, revalidation, synonymies, and new records in Bebelis Thomson (Coleoptera, Cerambycidae, Lamiinae, Apomecynini) - Santos-Silva, Antonio (Zootaxa, 2022)
Six new species of Bebelis Thomson, 1864 are described: B. wappesi, B. tinga, and B. skillmani, from Bolivia (Santa Cruz); B. nearnsi, from Bolivia (La Paz); B. parana, from Argentina (Corrientes); and B. imitatrix, from Argentina (Mendoza). Bebelis concisa Galileo & Martins, 2006 and B. angusta (Fisher, 1947) are synonymized with B. modesta (Belon, 1903); B. inaequalis (Fisher, 1947) is synonymized with B. obliquata (Breuning, 1940); B. schwarzi (Fisher, 1947) is synonymized with B. picta Pascoe, 1875; and B. acuta geometrica (Bates, 1880) and B. laetabilis (Belon, 1903) are synonymized with B. acuta Pascoe, 1875. New states records for B. angusta and B. cuprina (Belon, 1903) are provided. Bebelis zeteki (Fisher, 1947) is revalidated and Bebelis aurulenta (Belon, 1903) is illustrated for the first time. A provisional key to species of Bebelis is provided.